2014
DOI: 10.1080/10665684.2014.958965
|View full text |Cite
|
Sign up to set email alerts
|

More Than a Metaphor: The Contribution of Exclusionary Discipline to a School-to-Prison Pipeline

Abstract: The term and construct "school-to-prison" pipeline has been widely used by advocates, researchers, and policymakers to describe the relationship between school disciplinary practices and increased risk of juvenile justice contact. It has been unclear whether the construct is a useful heuristic or a descriptor of empirically validated relationships that establish school disciplinary practices as a risk factor for negative developmental outcomes, including juvenile justice involvement. In this article, we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
295
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 417 publications
(311 citation statements)
references
References 48 publications
8
295
0
8
Order By: Relevance
“…An important form of differential treatment based on ethnic or racial status are disciplinary practices. Some have argued that the disciplinary practices in United States are preparing African American, Latino, and Native American students for prison more directly than for higher education (e.g., Goffman, 2009; see also Skiba, Arredondo, & Williams, 2014). Beginning nearly 25 years ago, schools have relied on harsher disciplinary practices in schools despite little evidence that these harsh practices were justified.…”
Section: Differential Treatmentmentioning
confidence: 96%
See 2 more Smart Citations
“…An important form of differential treatment based on ethnic or racial status are disciplinary practices. Some have argued that the disciplinary practices in United States are preparing African American, Latino, and Native American students for prison more directly than for higher education (e.g., Goffman, 2009; see also Skiba, Arredondo, & Williams, 2014). Beginning nearly 25 years ago, schools have relied on harsher disciplinary practices in schools despite little evidence that these harsh practices were justified.…”
Section: Differential Treatmentmentioning
confidence: 96%
“…Research has found that these practices have increased the connection between school disciplinary practices and eventual contact with the juvenile justice system (Skiba et al, 2014). Of particular interest for our purposes is that the harsh disciplinary practices disproportionately target African Americans boys and girls, as well as Latino and American Indian boys (Skiba, Arredondo, & Williams, 2014).…”
Section: Quintana and Mahgoubmentioning
confidence: 98%
See 1 more Smart Citation
“…Such attention is warranted; there is a growing body of evidence indicating that racial inequities in out-of-school suspension and expulsion contribute to lower academic, behavioral, and social outcomes for recipient students of color (e.g., Skiba et al, 2003). Advocates and researchers alike have argued that poor relationships between students of color and school adults are one root cause of racial discipline gaps, and recommend that educators increase their focus on the affective dimensions of schooling (Carter, Fine & Russell, 2014).…”
mentioning
confidence: 99%
“…Another important factors is that these severe measures do not appear to discriminate between socio-economics status, as minorities are more likely to be suspended and expelled in equal percentage from affluent schools (Skiba & Losen, 2016). In addition, recent data shows other minority groups, such as the disabled, black and Latina females, and LBGT students, are also the target of more severe punishment (Skiba, Arredondo, & Williams, 2014 cameras and security personnel, including the creation of police forces by many school districts. However, studies have shown that these measures have provided very little relief in the decrease of violent and disruptive behavior (Skiba & Losen, 2016).…”
Section: The "Get-tough" Legacymentioning
confidence: 99%